Facing toward the dawn : the Italian anarchists of New London - Lenzi, Richard (SUNY series in Italian/American culture., 2019)
"Facing toward the Dawn is a history of the Italian American anarchist movement that existed in the Fort Trumbull neighborhood of New London, Connecticut, for seventy years. The Italian American radical movement thrived into the 1920s in industrial cities throughout the country. Connecticut possessed a vibrant movement, and New London's anarchists stood at the forefront of this activity. Based upon immigrants from the Marche region of Italy, especially the city of Fano, the Fort Trumbull anarchist groups maintained a strong, stable presence in the neighborhood for decades. Beginning as a circle within the ideological camp of Errico Malatesta, the New London Marchegian anarchists evolved into one of the core groupings within the wing of the movement supporting Luigi Galleani. They conducted manifold activities, from propaganda to involvement in the labor movement, fought fascists in the streets, held countless social events such as festas, theatrical performances, picnics and dances, and hosted militant speakers such as Emma Goldman. Above all, they established what could be called a "solidarity" subculture upon which the longevity of their group was based. This study is a micro-history of an ethnic radical group in a New England city during the heyday of labor radicalism in the United States, and written in the context of developing trends within the larger radical movement, the Italian American community, and greater American society as it moved from the Gilded Age to the New Deal and beyond"--